Phases I–III Clinical Trials Using Adult Stem Cells - Ricardo Sanz-Ruiz; Enrique Gutiérrez Ibañes; Adolfo Villa Arranz; María Eugenia Fernández Santos; Pedro L. Sánchez Fernández; Francisco Fernández-Avilés (Stem Cells International)
First randomized clinical trials have demonstrated that stem cell therapy can improve cardiac recovery after the acute phase of myocardial ischemia and in patients with chronic ischemic heart disease. Nevertheless, some trials have shown that conflicting results and uncertainties remain in the case of mechanisms of action and possible ways to improve clinical impact of stem cells in cardiac repair. In this paper we will examine the evidence available, analyze the main phase I and II randomized clinical trials and their limitations, discuss the key points in the design of future trials, and depict new directions of research in this fascinating field.